Can Mothers Afford to Work in Poland? : Labor Supply Incentives of Social Benefits and Childcare Costs - Bargu, Ali (World Bank, Washington, DC, 2018)
This paper analyzes the incentives to labor supply faced by families, particularly mothers, with young children in the context of a recently introduced fertility promotion benefit in Poland. The paper is based on an adapted version of the Organisation for Economic Co-operation and Development's Tax-Benefit Model, which estimates households' net earnings after taxes and social transfers at different levels of wages. Since the recent introduction of the 500 benefit, some households face steep marginal tax rates due to the benefit withdrawal rules. Single parents with two children, and second earners with one child can expect their income to increase by only 30 and 25 percent of the minimum wage, respectively, if they take up a job at minimum wage. If they must also pay for childcare, having all adults working can cause losses of up to 30 percent compared with if one adult stayed home. Although the 500 program radically contributed to reducing child poverty, in the absence of complementary reforms, these disincentives could affect more than half a million households, disproportionately in the lowest quintile. Vouchers for private childcare have been adopted by some municipalities in Poland to counter unmet demand for public nurseries. A 75 percent subsidy of typical childcare costs would restore the financial viability of low-paying work for mothers with young children. Alternative remedies include a reform of the eligibility and withdrawal rules of the 500 program.